2011
DOI: 10.1111/j.1440-1843.2011.01954.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between asthma control status, the Asthma Control Test™ and urgent health‐care utilization in Asia

Abstract: The GINA control classification and the ACT are valid symptom-based measures that are significantly associated with urgent health-care utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Studies using similar methods to the ones we used to evaluate the correlation of the ACT and the GINA classification are rare. Still Lai et al 16 recently found significant but lower (0.442) correlation between the ACT scores and a GINA-derived control index, whereas Thomas et al found moderate agreement between the ACT and GINA derived asthma control status 14 and found the ACT to be useful in predicting GINA-defined partly controlled/uncontrolled asthma.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Studies using similar methods to the ones we used to evaluate the correlation of the ACT and the GINA classification are rare. Still Lai et al 16 recently found significant but lower (0.442) correlation between the ACT scores and a GINA-derived control index, whereas Thomas et al found moderate agreement between the ACT and GINA derived asthma control status 14 and found the ACT to be useful in predicting GINA-defined partly controlled/uncontrolled asthma.…”
Section: Discussionmentioning
confidence: 93%
“…These findings were remarkably similar to those found by Thomas et al 14 , who included a large number of European and US asthma patients. Other studies using the ACT to assess control found yet higher numbers of uncontrolled asthma, with results ranging from 55% in a web-based study in the US 15 to 56% in a most recent Asian study 16 and up to 57% in European patients recruited over the internet 17 .…”
Section: Discussionmentioning
confidence: 97%
“…Also, as in other studies, we found that patients with uncontrolled or partially controlled asthma are at higher risk for hospitalization. (16)(17)(18) The proportion of patients who visited the emergency room was also higher among those with uncontrolled or partially controlled asthma (57.5% and 62.0%, respectively) than among those with 537 knowing that the disease is not controlled only on the basis of the questionnaire is enough of a warning to our health care system, given that the proportion of patients was high. Finally, these data were obtained from self-reports, i.e., they were not extracted from medical records.…”
Section: Discussionmentioning
confidence: 97%
“…[21][22][23] The lower direct cost in HCMC was due to the inexpensive health care services, cheaper medications and lower hospitalisation rate when the patients used controllers. 3,13,24 The increased rate of controlled asthma in our study also contributed to the decrease in direct health care costs. This is in agreement with the fi ndings in the AIRIAP study, which showed that the direct cost signifi cantly decreased when the levels of asthma control based on ACT improved.…”
Section: Public Health Action Implementation Of Gina Guidelines In VImentioning
confidence: 89%
“…However, primary care physicians at these centres have historically managed asthma using outdated treatment approaches, often only prescribing reliever medications (short-acting bronchodilators) when patients have asthma attacks and under-prescribing controller medications. Consequently, the proportion of patients with controlled asthma in Viet Nam is about 2.9%, 3 which falls markedly short of the goal of asthma …”
Section: Discussionmentioning
confidence: 99%